Competitive benchmarking of hotels’ service quality using analytic hierarchy process - Engku Abu Bakar, Engku Muhammad Nazri (2015)
In the wake of increasing competition, a growing number of hotels have begun to realize the importance of service improvements that can be converted to a competitive advantage. One way in which hotel managements may innovate and learn, as they respond to their competitive environment, is by means of benchmarking.Current practice in hotel benchmarking involves gauging guests‘ satisfaction and perception through either guests comment cards or reports from the hotels‘ guest satisfaction studies conducted by an outside firm.These approaches unfortunately do not measure the hotel‘s performance against that of competing hotels.Thus, in this study, we proposed the use of Analytic Hierarchy Process to comparatively benchmark any hotel against its competitors.We applied the technique to comparatively rank eight hotels along the Batu Feringghi and Tanjung Bungah beach areas in Penang, Malaysia.The hotels were ranked based on four key main attributes namely, the hotel, the front-office personnel, other than the front-office personnel, and the room values. Four members were asked to check in at all the hotels for two nights each and do pairwise comparison evaluations on all the attributes and sub-attributes as well as pairwise comparison evaluations on the hotels with regards to each attribute and sub-attribute.The results obtained from the comparison processes were the rankings or the relative standings of each hotel compared to the other hotels with regards to each attribute, sub-attribute and the combination of all the attributes and subattributes.The output from this study provides a useful framework for operationalizing the level of competition in the hotel industry in the sense that the output helps the hotel manager to determine where the hotel stands on service performance relative to its competitors and, consequently, identify specific areas of comparative advantages and disadvantages.